Evaluation of the effects of wheat gluten source and animal plasma blends on the growth performance of nursery pigs - Lawrence, K.R.; Hanni, S.M.; Groesbeck, C.N.; Hastad, C.W.; Young, M.G.; James, B.W.; Keegan, T.P.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 472 weanling pigs (initially 13.5 lb) were used in two experiments to evaluate the effects of wheat gluten source (WG) and combinations with spray-dried animal plasma (SDAP) on growth performance of nursery pigs. In Exp. 1, the five dietary treatments included a control diet containing 6% SDAP, wheat gluten that was enzymatically hydrolyzed (Source 1), and a non-hydrolyzed wheat gluten (Source 2). The wheat gluten sources replaced L-lysine HCl and replaced 50% or 100% of the spray-dried animal plasma. From d 0 to 7, 7 to 14, and 0 to 21, increasing wheat gluten decreased (linear; P<0.05) ADG. There were no differences between wheat gluten sources. Average daily feed intake decreased similar to ADG, with the exception that ADFI of pigs fed wheat gluten Source 2 had only a slight decreasing trend (P<0.11) from d 0 to 7. Pigs fed the diet containing 6% SDAP had the greatest ADG and ADFI from d 0 to 21. When the SDAP was replaced with either wheat gluten source, ADG and ADFI linearly decreased (P<0.01) but F/G improved (P<0.04). When pigs were fed the common diet from d 21 to 35, there were no differences (P<0.05) in ADG, ADFI or F/G. In Exp. 2, the six dietary treatments included a negative control with no SDAP or WG (0:0 ratio), 9% WG (100:0 ratio), 6.75% WG and 1.25% SDAP (75:25 ratio) combination, 4.5% WG and 2.5% SDAP (50:50 ratio) combination, 2.25% WG and 3.75% SDAP (25:75 ratio) combination, and a positive control with 5% SDAP (0:100 ratio). The wheat gluten (Source 1) was enzymatically hydrolyzed, but from a different lot than Exp. 1. From d 0 to 14, pigs fed 6% SDAP had numerically greater ADG and ADFI compared to pigs fed the negative control diet. However, replacing SDAP with increasing amounts of WG tended to decrease (P<0.10) ADG and ADFI. These results confirm the improved ADG and ADFI of pigs fed SDAP immediately after weaning. In these experiments, replacing SDAP with WG resulted in decreased ADG.
Keywords: Wheat gluten; Spray-dried animal plasma; Nursery pigs; Swine